2006
DOI: 10.1179/174329306x107674
|View full text |Cite
|
Sign up to set email alerts
|

Observation of hybrid (cw Nd:YAG laser + MIG) welding phenomenon in AA 5083 butt joints with different gap condition

Abstract: In recent time there has been vigorous development of laser hybrid welding technology for applications in numerous industrial fields. Many of those research achievements have already been reported to relevant technology users. However, there are many issues still requiring further research and development, including more comprehensive understanding of the various welding phenomena in laser hybrid welding. In the present study, therefore, the laser hybrid welding process was examined using high speed video in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Zhang et al examined the microstructure of AA6061 aluminum alloys using ER4043 filler wire by 4 kW Nd:YAG laser-MIG hybrid welding [13]. Kim et al studied the welding phenomenon in AA 5083 butt joints with different gap conditions by laser-MIG hybrid welding [14]. Furthermore, some studies explored the effects of shielding gas, laser beam diameter, and process stability on the tolerance of joint gap and bead shape in laser-MIG hybrid welding [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al examined the microstructure of AA6061 aluminum alloys using ER4043 filler wire by 4 kW Nd:YAG laser-MIG hybrid welding [13]. Kim et al studied the welding phenomenon in AA 5083 butt joints with different gap conditions by laser-MIG hybrid welding [14]. Furthermore, some studies explored the effects of shielding gas, laser beam diameter, and process stability on the tolerance of joint gap and bead shape in laser-MIG hybrid welding [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al (2006) carried out a series of CO 2 laser-gas metal arc (GMA) hybrid welding experiments to study the effects of laser power, arc current, and the stand-off distance between laser and arc on the melting energy of CO 2 laser-GMA hybrid welding. Kim et al (2006) observed the hybrid laser-MIG welding phenomenon in butt joints with different gap conditions by using a high speed camera. Qin et al (2007) experimentally investigated the effects of Nd:YAG laser and pulsed MAG arc hybrid welding parameters on the weld shape.…”
Section: Introductionmentioning
confidence: 99%
“…High speed imaging has enabled the study of drop transfer and the keyhole conditions for steel 10,11 and aluminum. 12,13 It has been established that the recoil pressure from keyhole evaporation can drive the melt into the gap. 10 Different situations have been classified 13 dependent on the presence of a gap, the torch arrangement, and the corresponding drop flight and heat and mass transfer.…”
Section: Introductionmentioning
confidence: 99%